2015
DOI: 10.1134/s1995425515040034
|View full text |Cite
|
Sign up to set email alerts
|

Ecological interactions in the system: Entomopathogenic bacterium Bacillus thuringiensis—phytopathogenic fungus Rhizoctonia solani—host plant Solanum tuberosum

Abstract: The mutual functional dependence in the three component system Bacillus thuringiensis-Rhizoc tonia solani-Solanum tuberosum is shown. Suppression of the rhizoctonia potato disease due to the treatment of tubers with entomopathogenic bacteria Bacillus thuringiensis subsp. Darmstadiensis (BtH 10 ) is demon strated. In vitro inhibitory activity of BtH 10 towards R. solani exceeded 80%. Field testing is carried out on two potato cultivars of different ripeness groups in 2013-2014. The rhizoctonia disease severity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…TS2, B. thuringiensis B-5351, and B. thuringiensis B-6066, which increased the weight of large tubers, the formation of small tubers was lower than of control plots. Similar results were reported by Bakhvalova et al (2015) , who showed that the biomass of potato tubers was increased under the influence of B. thuringiensis H10 strain due to the enhancement of quantity and weight of tubers in ≥ 80-g class, and distribution of Rhizoctonia on potato stolons decreased almost twice. Soil drenching with B. subtilis KU936344, KU936345, and KU936341 strains led to the higher yield of market-grade potato tubers and less unfit for trading tubers, even when compared with plots treated with fungicide Mancozeb ( Kumbar et al, 2019 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…TS2, B. thuringiensis B-5351, and B. thuringiensis B-6066, which increased the weight of large tubers, the formation of small tubers was lower than of control plots. Similar results were reported by Bakhvalova et al (2015) , who showed that the biomass of potato tubers was increased under the influence of B. thuringiensis H10 strain due to the enhancement of quantity and weight of tubers in ≥ 80-g class, and distribution of Rhizoctonia on potato stolons decreased almost twice. Soil drenching with B. subtilis KU936344, KU936345, and KU936341 strains led to the higher yield of market-grade potato tubers and less unfit for trading tubers, even when compared with plots treated with fungicide Mancozeb ( Kumbar et al, 2019 ).…”
Section: Discussionsupporting
confidence: 89%
“…On the day of harvest, the tubers were classified into three fractions—small (tubers < 50 g), seed (tubers between 50 and 80 g), and large (tubers > 80 g)—and weighed separately. Data on the productivity of potatoes were prepared according to Bakhvalova et al (2015) .…”
Section: Methodsmentioning
confidence: 99%
“…Also, microorganisms are involved in soil processes and the formation of their properties. In summary, the presented results are in line with current trends in the use of a mixture of bioagents for plant protection from harmful organisms to improve the effectiveness of biological plant protection, including inducing systemic resistance to the pathogen [14]. International Journal of Agronomy…”
Section: E Effect Of the Drug Phytop 2682 On The Phytopathogenic Microflora Of The Soilsupporting
confidence: 80%
“…Several plant-associated bacteria are shown to be antagonistic towards plant-pathogenic fungi. Potato tubers treated with Bacillus thuringiensis proved to suppress rhizoctonia potato disease (Bakhvalov et al 2015).…”
Section: Plant Healthmentioning
confidence: 99%